PERTUMBUHAN STEK BATANG CINCAU HIJAU (Premna oblongifolia Merr) AKIBAT PEMBERIAN PUPUK ORGANIC CAIR DAN PUPUK NPK PADA TANAH GAMBUT - Sulistiyanto, Yustinus; Zubaidah, Siti (AgriPeat, 2021)
Green cincau (Premna oblongifolia Merr) is a functional food plant that needs to be developed because it functions as a refreshing plant and has high chlorophyll content to increase endurance and its phytochemical content which is useful for overcoming various diseases. Green cincau (Premna oblongifolia Merr) in peat soils have not been widely cultivated due to the constraints of low soil fertility. This research is basic research aiming to determine the effect of using liquid organic fertilizers and inorganic fertilizer on the growth of green cincau in peat soil. The research was conducted in the greenhouse of the Department of Agronomy and soil analysis was carried out at the UPR Integrated Laboratory. This research used a factorial completely randomized design (CRD) consisting of 2 factors, namely factor I (Liquid Organic Fertilizer) consisting of 3 types, namely: P0 = without liquid organic fertilizer; P1 = Agrobost liquid organic fertilizer; P2 = Nasa liquid organic fertilizer; Factor II (NPK Inorganic Fertilizer) which consists of 3 levels, namely: N0 = NPK 0 g polibag-1; N1 = NPK 1 g polibag-1; N2 = NPK 2 g polibag-1. There were 9 treatment combinations, the replication was carried out 3 times so that there were 27 experimental units. Growth observation variables included a number of shoots, shoot length, number of leaves, leaf area, leaf fresh weight, number of roots, root length, and root fresh weight. Data were analyzed by analysis of variance (F test) at the 5% level, if the effect was significant, then tested it with the 5% BNJ test. The results showed that the interaction of liquid organic fertilizer and NPK inorganic fertilizer did not significantly affect all variables. The application of liquid organic fertilizer affects the number of leaves, leaf area, leaf fresh weight, number of roots and root fresh weight. Nasa organic fertilizer provides better growth than Agrobost with 13.42 leaves shoots-1, 2,623.40 cm2 leaf area polibag-1, 47.02 g polibag-1 fresh leaf weight, 12 roots number polibag-1 and 1.55 root weight g polibag-1. NPK inorganic fertilizer at a dose of 2 g polibag-1 resulted in better leaf fresh weight, namely 45.64 g polibag-1